2020
DOI: 10.13171/mjc101020291172ja
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of aluminum-based adsorbent and application in fluoride removal from aqueous solution

Abstract: A novel adsorbent was obtained by a facile precipitation method and was used for fluoride removal from aqueous solution. Mineralogical and physicochemical characterization of the adsorbent was carried out by X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), Energy Dispersive X-Ray attached to Scanning Electron Microscopy (SEM-EDX), BET Specific Surface Area(SSAN2BET) analysis and Fourier-Transform Infrared Spectrometry (FTIR). The effect of various operational parameters such as contact time, initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The experimental data indicated that the uoride removal was greater than 95% in the pH range of 3-12, except for pH 11, where the lowest value was 88.42%. Overall, the degree of uctuation in uoride removal e ciency was minimal, indicating that the pH dependence of uoride adsorption on CDAA was insigni cant (Assaoui, et al, 2020). It is noteworthy that the residual uoride concentration after de uoridation was consistently less than 0.3 mg/L at pH levels of 3-10 and 12, which was signi cantly lower than the WHO-speci ed drinking water uoride content of 0.7 mg/L.…”
Section: Effect Of Initial Ph and Zeta Potentialmentioning
confidence: 89%
See 2 more Smart Citations
“…The experimental data indicated that the uoride removal was greater than 95% in the pH range of 3-12, except for pH 11, where the lowest value was 88.42%. Overall, the degree of uctuation in uoride removal e ciency was minimal, indicating that the pH dependence of uoride adsorption on CDAA was insigni cant (Assaoui, et al, 2020). It is noteworthy that the residual uoride concentration after de uoridation was consistently less than 0.3 mg/L at pH levels of 3-10 and 12, which was signi cantly lower than the WHO-speci ed drinking water uoride content of 0.7 mg/L.…”
Section: Effect Of Initial Ph and Zeta Potentialmentioning
confidence: 89%
“…An ion selective uoride electrode (PXSJ-216F, LEICI, China) was used for uoride determination. To avoid the in uence of other ions, the total ionic strength adjustment buffer (TISAB) is commonly mixed with the test solution prior to measurement (Assaoui, et al, 2020;De Silva, et al, 2020).…”
Section: Characterization and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various technologies are available for the removal of fluorides, including precipitation, coagulation, reverse osmosis, ion exchange, and adsorption. Of all methods, adsorption is highly effective and economical for the reduction of excess fluoride in water (Abeykoon et al 2020;Akafu et al 2019;Alkurdi et al 2019;Assaoui et al 2020;Emmanuel et al 2018;Fan et al 2019), and it uses a variety of adsorbent materials, including clay, soil, organic matter, alumina, zeolites, nanomaterials, activated carbon and bone char (Alkurdi et al 2019;Teusner et al 2016). Bone chars have been widely considered in fluoride removal and have gained considerable attention due to their cheapness, high availability, easy preparation and high adsorption capacity (Alkurdi et al 2019;Medellin-Castillo et al 2020).…”
Section: Introductionmentioning
confidence: 99%